Measuring maintenance performance of food court under local authority : Ipoh City Council, Perak Malaysia / Nuriffah Ruslan and Junainah Mohamad - Ruslan, Nuriffah; Mohamad, Junainah (2019)
Measuring maintenance performance is fundamental aspect in maintenance management. One of the key issues in maintenance management is to ensure all the maintenance activities planned and executed have given the expected results and satisfied all the users. This can be measure by using maintenance performance indicators such as functional, technical and images. The aim of this paper is to measure the maintenance performance level of food court under Ipoh City Council, Perak Malaysia. A quantitative method was adopted with the selection of Medan Selera Stadium Ipoh as the case study. Medan Selera Stadium Ipoh covered the population of 70 food court's tenants, but only 59 food court's tenants being selected as the respondents. The total of 59 questionnaires was distributed to the food court's tenants and the finding shows that most of the food court's tenants satisfied with the service delivered by Ipoh City Council.